PWE-018 Hspc1 Inhibitors Potentiate The Effect Of 5-fu In Primary Colorectal Cancer Cell Model. (9th June 2014) - Lee, SL; Dempsey-Hibbert, NC; Sutton, P; Vimalachandran, D; Wardle, TD; Williams, J
Abstract : Introduction: Colorectal cancer (CRC) is the fourth most common cancer in the UK and was responsible for more than 15, 000 deaths in 2011. 1 Less than 50% of patients with Dukes stage C and D survive more than 5 years. 2 Molecular chaperone Heat shock protein (HSP) C1 is elevated in CRC. 3 HSPC1's client proteins (e.g., HER2, pNF-ĸB, Akt etc.) are involved in key cellular pathways and apoptosis. HSPC1 inhibitors recently showed positive clinical results in breast cancer 4 and non-small cell lung carcinoma. 5 This study aims to explore the effect of combining HSPC1 inhibitors with 5-fluorouracil (5-FU), the mainstay chemotherapy, in CRC. Methods: CRC cell line HT29 were treated with HSPC1 inhibitors 17-DMAG and NVP-AUY922 as single agent and in combination with 5-FU. Six primary CRC samples were obtained immediately following surgical resection with consent and treated with HSPC1 inhibitors. Four subsequent samples were treated with a combination of HSPC1 inhibitors and 5-FU. Following treatment, cell metabolism rate and apoptosis were assessed using MTS and caspase-3 assay. Results: In HT29, 17-DMAG was effective in inducing apoptosis and reducing cell proliferation whereas NVP-AUY922 did not. When combined with 5-FU, 17-DMAG showed additive effect. In primary CRC cells, a 50% reduction in cell metabolism rate was observed in 2/6 samples for 17-DMAG and 1/5 samples for NVP-AUY922. When subsequent primary samples were treated with 5-FU and HSPC1 inhibitors, significant decrease in cell metabolism rate and increase in apoptosis were observed in 1/4 samples. Conclusion: HSPC1 inhibitors are able to potentiate the chemotherapeutic effect of 5-FU in CRC cell line and this result may be replicated in primary colorectal cancer cells obtained from surgical specimen. HSPC1 inhibitors have different mode of actions which is evident in the different response observed in both HT29 and primary cells. In addition, CRC cells have individual response to HSPC1 inhibitors and some were not responsive. Although a small sample size, this study encouraged our next phase of research combining HSPC1 inhibitors with current chemotherapeutic agents including oxaliplatin and irinotecan. Further studies will also focus on identifying potential biomarkers to select susceptible patients. References: Cancer Research UK, 2013 National Cancer Intellidence Network (NCIN), 2009 Milicevic, Z, et al . International Journal of Oncology 2008. 32(6):p. 1169–1178 Modi, S, et al . Clin Cancer Res 2011;17(15):5132–9 Sequist, LV, et al . J Clin Oncol 2010:28(33):4953–60 Disclosure of Interest: None Declared.